On Different Views On The Mechanism Of Tissue Thermogenesis And Endothermity Of The Body - Мавланова Садбархон Акаримовна; Mirzaolimov Mirzokhid Mirzavalievich (Genius Journals, 2024)
The review discusses the mechanisms of thermogenesis in animal tissues, including mitochondria, which provide the endothermic state of the body. Previous views on thermogenesis were largely based on the idea of a low efficiency of biological processes. Subsequently, data were gradually accumulating on the possibility of a sufficiently high efficiency of these processes. Otherwise, there would be no cold-blooded organisms with a low level of metabolism and high efficiency.
Keywords: metabolism; organisms; possibility; efficiency